Bactericidal antibiotics promote oxidative damage and programmed cell death in sinonasal epithelial cells. Issue 4 (24th January 2017) - Kohanski, Michael A.; Tharakan, Anuj; London, Nyall R.; Lane, Andrew P.; Ramanathan, Murugappan
Abstract : Background: Antibiotics are widely and heavily used in the treatment of chronic sinusitis. Bactericidal antibiotics can stimulate reactive oxygen species (ROS) formation, a proinflammatory response, and cell death in cultured human sinonasal epithelial cells (SNECs). Sulforaphane (SFN) is a potent stimulator of the antioxidant nuclear factor erythroid 2‐related factor 2 (Nrf‐2) system and a suppressor of inflammation. In this study we utilized SFN to further explore the relationship between levofloxacin treatment, ROS formation, and the cell death response. Methods: SNECs were collected from patients during endoscopic sinus surgery and grown in culture at the air‐liquid interface. Differentiated SNECs were stimulated with levofloxacin with or without SFN pretreatment. ROS were quantified. Apoptosis markers of caspase‐3 activity and DNA fragmentation were quantified. Results: Cultured SNECs treated with levofloxacin resulted in a significant increase in activity of the proapoptotic caspase‐3 protease (5.9‐fold, p = 0.01). The increase in activity was suppressed by pretreatment with SFN (1.9‐fold). ROS levels increased with levofloxacin treatment (range, 1.2‐fold to 1.8‐fold), but were not significantly suppressed by pretreatment with SFN (range, 1.0‐fold to 1.3‐fold). Conclusion: In this study, we demonstrate that treatment of cultured SNECs with levofloxacin leads to an increase in caspase‐3 activity. SFN pretreatment suppresses the increased apoptotic response possibly through its antioxidant stimulating properties. Our results suggest that levofloxacin treatment stimulates a potent proapoptotic possibly through an ROS‐dependent mechanism. Future studies will explore if this antibiotic‐induced response is harmful to recovery of function in those with sinusitis.